Academic identity in a changing Australian higher education space: the higher education in vocational institution perspective. (3rd May 2020) - Sinclair, Alice; Webb, Sue
ABSTRACT: This article explores the academic identities of college educators of higher education in vocational institutions. Qualitative semi-structured interviews generated data from eleven educators in five vocational education institutions. Discourse analysis revealed that educators distinguished their vocational institutions' contributions to HE as different, but equal or superior to those of universities. Educators presented their culture and practices in advantageous ways, contrasted against imagined stereotypes of university experiences, which are perceived to be deficient for supporting the types of students they teach. In adopting academic identities that distinguish their cultures and practices from those presumed prevalent in universities, these educators seek parity of esteem with universities through distinctiveness, and reject research-focused academic identities and academic drift. In embracing teacherly identities supporting students rather than the research-teaching nexus, educators may be contributing to the 'therapeutic turn', diminishing opportunities for students, and furthering the vertical stratification of institutions within the Australian HE space.